2018
DOI: 10.1007/s41030-018-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Determination of the Main Effects in the Design of High-Flow Nasal Therapy Systems with Respect to Aerosol Performance

Abstract: Introduction: The use of concurrent aerosol delivery during high-flow nasal therapy (HFNT) may be exploited to facilitate the delivery of a variety of prescribed medications for inhalation. Until now, a systematic approach to determine the conditions required to yield an optimal emitted dose has not been reported. The aim of this study was to establish the effects of gas flow rate, input droplet size, and nebulizer position on the amount of aerosol exiting the nasal cannula during HFNT and thus becoming availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 29 publications
6
30
1
Order By: Relevance
“…Previously our group reported a systematic approach to determine the conditions required to yield an optimal emitted dose, thus becoming available for inhalation during HFNT [20]. The findings in that study clearly indicate that in order to optimize the amount of aerosol exiting the nasal cannula interface during HFNT, it is necessary for gas flow to be low and the input droplet size to be small, while the nebulizer should be positioned immediately after the humidification chamber [18].…”
Section: Introductionmentioning
confidence: 89%
“…Previously our group reported a systematic approach to determine the conditions required to yield an optimal emitted dose, thus becoming available for inhalation during HFNT [20]. The findings in that study clearly indicate that in order to optimize the amount of aerosol exiting the nasal cannula interface during HFNT, it is necessary for gas flow to be low and the input droplet size to be small, while the nebulizer should be positioned immediately after the humidification chamber [18].…”
Section: Introductionmentioning
confidence: 89%
“…Non-invasive Nasal High Flow therapy is increasingly used across a variety of patient populations and so it may be beneficial to combine this intervention with inhaled drug therapy including biomolecules [28]. Investigations by Branconnier and colleagues [29] determining non-invasive nasal high flow therapy-nebulizer compatibility employed albuterol sulphate as an exemplar drug, as have studies by Diaz and colleagues [25], and our own colleagues [30]. We chose to use albuterol as a tracer aerosol (see study limitations).…”
Section: Methodsmentioning
confidence: 99%
“…An adult high flow nasal therapy system (Optiflow™, Fisher and Paykel) was attached to a humidifier (MR850™, Fisher and Paykel) set at 37 °C. The nebulizers were placed at the humidifier, in line with previous findings for maximal aerosol delivery during high flow therapy [30]. 2 ml of 2 mg/ml Albuterol sulphate solution was nebulized by both the Aerogen Solo and PDAP mesh devices.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our group reported a systematic approach to determine the conditions required to yield an optimal emitted dose, thus becoming available for inhalation during HFNT. The findings in that study clearly indicate that in order to optimize the amount of aerosol exiting the nasal prongs during HFNT, it is necessary for the gas flow rate to be low and the input droplet size to be small, while the nebulizer should be positioned immediately after the humidification chamber [13]. In a recent scintigraphy study, Dugernier et al demonstrated in vivo that lung deposition was significantly greater while using a vibrating mesh nebulizer (VMN), in comparison with a jet nebulizer (JN) during adult HFNT [14].…”
Section: Introductionmentioning
confidence: 99%